Drug sensitivity of clinical isolates of Mycobacterium tuberculosis and its association with bacterial genotype in the Somali region, Eastern Ethiopia - Worku, Getnet; Gumi, Balako; Girma, Musse; Mohammedbirhan, Binyam; Diriba, Getu; Seid, Getachew; Getu, Melak; Amare, Misikir; Sinshaw, Waganeh; Ashagre, Wondimu; Tschopp, Rea; Carruth, Lauren; et al. (Frontiers in Public Health, 2022)
Background Drug resistance is becoming a major bottleneck for tuberculosis (TB) control programs in countries with high TB burdens. Although several studies were conducted on the drug sensitivity of Mycobacterium tuberculosis (M. tuberculosis) in central Ethiopia, there is a lack of data on the drug sensitivity of M. tuberculosis in the peripheral regions of the country including in the Somali region. Therefore, the objective of this study was to evaluate the drug sensitivity of M. tuberculosis and its association with bacterial genotype and evaluate the performance of Xpert MTB/RIF (Xpert) in detecting resistance to rifampicin (RIF). Methods A total of 302 M. tuberculosis were tested using the BD BACTEC-Mycobacteria Growth Indicator Tube 960 (MGIT 960) system for their drug sensitivity to the first-line anti-TB drugs. Besides, the drug sensitivity of 10 multidrug-resistant (MDR) M. tuberculosis isolates was evaluated for the second-line anti-TB drugs. Additionally, 177 of the 302 isolates were tested for genotypic drug resistance using Xpert. Chi-square and Fisher's exact tests were used for the evaluation of the association between variables and drug sensitivity. Results The overall prevalence of resistance to at least one drug was 11.6% (95% CI: 7.9–15.2%), while the prevalence of MDR was 3.3% (95% CI: 1.3–5.3%). Two of the 10 MDR isolates were resistant to capreomycin. The spoligotype Shared International Type (SIT) 149 was significantly associated with either monoresistance or MDR (p < 0.05). Of the 177 isolates tested by Xpert, 6.2% (11/177) were RIF-resistant. Discordant between Xpert and MGIT 960 was observed in one isolate and linked with probe-binding delay (ΔCT max = 5.8). The sensitivity and specificity of the Xpert assay were 100 and 99.4%, respectively, while its positive and negative predictive values were 90.9 and 100%, respectively. Conclusion The magnitude of MDR M. tuberculosis in the Somali region of Ethiopia was higher than the national prevalence of MDR-TB warranting the strengthening of the TB control program in the Somali region. Besides, drug resistance was associated with SIT 149 spoligotype (genotype). The Xpert assay was observed to have high sensitivity and specificity in detecting RIF-resistant M. tuberculosis, which is encouraging for its application widely.